New insight into δ-Pu alloy oxidation kinetics highlighted by using in-situ X-ray diffraction coupled with an original Rietveld refinement method. (1st July 2018) - Ravat, B.; Jolly, L.; Oudot, B.; Fabas, A.; Guerault, H.; Popa, I.; Delaunay, F.
Graphical abstract: Highlights: In situ X-ray diffraction performed continuously during the oxidation process. Use of an original refinement Rietveld method for multilayered sample. Monitoring of the individual growth kinetics of the phases present in the oxide scale. The parabolic stage results mainly from the growth of an α-Pu2 O3 layer. The subsequent linear kinetics is related to accelerated growth of PuO2 scale. Abstract: The reactivity of a δ-Pu alloy was studied under dry oxygen at different temperatures. Phase analysis has shown the presence of α-and β-Pu2 O3, PuO2, as well as the destabilisation of the δ-phase. The oxidation kinetics were studied using in-situ X-ray diffraction coupled with an original method of Rietveld refinement enabling an individual monitoring of the growth of each oxide. The results have evidenced a parabolic stage resulting from the thickening of the α-Pu2 O3 layer, in which a compressive stress state develops. This stage is followed by the linear growth of a porous PuO2 scale.